The Effect of Providing Incentives on Employee Performance at the Makassar City Regional Drinking Water Company (PDAM) - Nurul Khusna; Andi Jam’an; Irwan Abdullah (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the effect of providing incentives on employee performance at the Makassar City Regional Drinking Water Company (PDAM). The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection techniques were carried out using questionnaires, observation and documentation. In this research, the data sources used in data collection include primary data and secondary data. The population in this study were 77 employees of the Regional Drinking Water Company of Makassar City. The sample used in this research was 77 respondents. The research instrument used in this research used the Likert scale (method). Based on the results of data research using statistical calculations through the Statistical for the Social Science (SPSS) version 26 application regarding the Effect of Providing Incentives on Employee Performance at the Makassar City Regional Drinking Water Company (PDAM) which was discussed previously, the author draws an important conclusion, (namely) that Incentives have an effect positive and significant on Employee Performance at the Regional Drinking Water Company (PDAM) of Makassar City as evidenced by the Incentive regression coefficient (X) value of 0.460 and the t count value of 8.759 > t table 1.665 with a significant value of 0.000 < 0.05.